At-Risk Populations for Osteosarcoma: The Syndromes and Beyond. (12th March 2012) - Calvert, George T.; Randall, R. Lor; Jones, Kevin B.; Cannon-Albright, Lisa; Lessnick, Stephen; Schiffman, Joshua D.
Abstract : Osteosarcoma is the most common primary malignancy of bone. Most cases are sporadic without a known genetic or environmental cause. Heritable genetic predisposition syndromes are associated with a small percentage of osteosarcomas. Study of these rare disorders has provided insight into the molecular pathogenesis of osteosarcoma. Screening of at-risk families and surveillance of affected individuals for these syndromes may permit earlier diagnosis and more effective treatment of osteosarcoma in these populations. This paper reviews the genetic and clinical features of the known osteosarcoma predisposition syndromes.